The lived experiences of cluster foster parents in Mhluzi Area in Middelburg, Mpumalanga Province, South Africa - Manamela, Nakedi Presley (My University, 2024)
The emergence of cluster foster parents occured as a growing number of children in need of care and protection due to a lack of responsible parents or the loss of their original parents. Cluster foster parents end up caring for children from diverse origins and with varying needs. Cluster foster parenting is an alternative care option for children who demand attention and protection. Furthermore, it offers cluster foster parents an environment that acknowledges their economic, social, educational, health, and cultural needs without bias. In summary, the primary purpose of cluster parenting is to protect children while they grow up in a safe, healthy, and accommodating setting. Regardless of the great impact made by cluster foster parenting, it has been established globally that cluster foster parenting has major shortcomings to the point that foster parents’ rights are not valued and ignored. Cluster foster parents are overwhelmed with high challenges daily, hence this study sought to explore the lived experiences of cluster foster parents. To achieve the study's main aim, the researcher used a qualitative approach as well as a phenomenological research design. Furthermore, within the non-probability sampling, the purposive sampling technique was followed to select fifteen cluster foster parents in Middelburg Mpumalanga Province. Data for the study were collected through a literature review and semi-structured interviews guided by an interview schedule with open-ended questions. Data were analysed thematically with the assistance of the NVivo programme. Guided by the social development approach the study explored the experiences of cluster foster parents fostering children with special needs, such as lack of knowledge in caring for cluster foster children, mental health issues encountered by cluster foster parents in caring for foster children, and a lack of support system. The findings revealed that cluster foster parents lack sufficient knowledge to work with foster children with special needs. The findings also indicated that working with children with uncontrollable behaviour drains cluster foster parents physically and emotionally and their mental health is at times compromised. One of the findings was that for cluster foster parents to perform their duties daily, they need a variety of support systems, including support from the undersigned social workers, churches, the Department of Social Development (DSD), Non-Governmental Organisations (NGOs), and family members. This collaboration enables them to cope, debrief, and carry out their daily obligations. Therefore, the study advanced recommendations that working with foster children and children with special needs requires a more effective working relationship between the cluster foster parents, designated social workers and in collaboration with various stakeholders. It is possible to conclude that caring for foster children with special needs is a reality that comes with a lot of good attitudes, responsibility, and accountability. However, cluster foster parents cannot execute such duties independently. Moreover, there is a need for a support system, and training and capacitating of cluster foster parents.
Thesis (M. Social Work) -- University of Limpopo, 2024
Keywords: Cluster foster parents.; Foster care; Foster child; Foster parents -- South Africa -- Mpumalanga; Foster children -- Care -- South Africa -- Mpumalanga; Child care services -- South Africa -- Mpamalanga